Molecular survey and microscopic examination of Hepatozoon Miller, 1908 (Apicomplexa: Adeleorina) in lacertid lizards from the western Mediterranean - Maia, João P M C; Perera, Ana; Harris, D James (Folia parasitologica, 2012)
The genus Hepatozoon Miller, 1908 (Apicomplexa: Adeleorina) is composed of intracellular haemogregarine parasites that are widely distributed among all tetrapod groups. The present study combines microscopic and molecular data on haemogregarine parasites from lizards in the western Mediterranean. We screened tissue samples and examined blood smears for the presence of species of Hepatozoon from four lizards, namely Algyroides marchi Valverde, endemic to Southeast Spain, Podarcis bocagei Seoane from Spain and Portugal, P hispanica Steindachner from Spain, and P lilfordi Günther from Cabrera, Balearic Islands (Spain). Our results show that prevalence and intensity of Hepatozoon parasites vary between and within lizard species from different regions. Algyroides marchi and P bocagei from Spain had the lowest values, whereas P hispanica had the highest. Phylogeny based on 18S rRNA gene sequences indicates that most of the new Hepatozoon sequences are part of a clade exclusive from North African and Iberian lizards, except for a single P bocagei isolate that is found related to another clade including isolates from other reptile host species and rodents. Interestingly, isolates from Algyroides form a distinct monophyletic subgroup, which could be a signal of strict host-specificity within this host genus.
Keywords: Animals; Středomoří; RNA, Ribosomal, 18S; Protozoan Infections, Animal; RNA protozoální; RNA, Protozoan; Genetic Variation; Phylogeny; Mediterranean Region; Lizards; RNA ribozomální 18S; protozoální infekce zvířat; ještěři; Apicomplexa; genetické markery; zvířata; fylogeneze; genetická variace; Genetic Markers